Gestión de aceites lubricantes usados en el cantón el Guabo - Armijos López, Jennifer Dennis (2018)
The use of lubricating oils has currently become the main problems worldwide due to the impact they cause to the environment due to its inadequate final disposal. In our country, the generation of dangerous products such as lubricating oils, is due to the ministerial treatments 026, 061, and to the ministerial treatments to follow. to obtain the approval of the Ministry of Environment of Ecuador through the Department of Environmental Quality. The index of the car park of the city El Guabo has grown considerably since 2010, currently has approximately 11,356 vehicles, with maintenance centers such as lubricators, mechanics and washing machines benefiting from this considerable considerable. In city El Guabo, has 24 automotive service centers, considering that 23 does not have the basic infrastructure necessary to operate as lubricators, mechanics and washing machines. The automotive service centers of city El Guabo, do not comply with the current environmental regulations on the management of hazardous waste, it is for that reason that it is a mechanism to facilitate the process of regularization and once they can reject impacts to the environment. In addition to studying the amount of lubricating oils that enter and leave the automotive service centers in order to know where the surplus lubricant used and what is its final destination remains. The main problems detected in our research work on lubricating oils used in the city El Guabo were three, taking into account the classification of hazardous waste with medium severity, the other problems at the time of the incident, the regularization of the activity , spill of used oil direct to the ground with a high severity.